Lie symmetry analysis and reductions of a two-dimensional integrable generalization of the Camassa-Holm equation - Kraenkel, Roberto André [UNESP]; Senthilvelan, M.; Zenchuk, A. I. (Elsevier B.V., 2000)
In this Letter we investigate Lie symmetries of a (2 + 1)-dimensional integrable generalization of the Camassa-Holm (CH) equation. Through the similarity reductions we obtain four different (1 + 1)-dimensional systems of partial differential equations in which one of them turns out to be a (1 + 1)-dimensional CH equation. We establish their integrability by providing the Lax pair for all of them. Further, we present a brief analysis for some types of particular solutions which include the cuspon, peakon and soliton solutions for the two-dimensional generalization of the CH equation. (C) 2000 Published by Elsevier B.V. B.V.